Energy Efficient Snubber Networks - Darwish, Mohammed K.; Marouchos, Christos; Janbey, Al; Amreiz, Hassan Musa (My University, 2019)
Conventional snubber networks which are used to remove the stress from semiconductor devices during turning-on and turning-off are used to shape the switching locus to keep it within the Safe Operating Area (SOA) and to reduce the turn-on and turn-off switching losses in the switching devices. Usually a large snubber inductance or capacitance is found to be effective in reducing the dissipation in a resistor. It would be more efficient if, after extracting the switching energy from the semiconductor device, to feed this energy somewhere useful instead of dissipating it as a heat. By doing so, the overall efficiency of the converter would be improved. This is the aim of energy-efficient snubber circuits which is presented in this paper.
Keywords: Semiconductor devices; Snubber circuits